2018
DOI: 10.1002/eat.22933
|View full text |Cite
|
Sign up to set email alerts
|

What position do you play? Eating disorder pathology among rugby players, and the understudied role of player position

Abstract: Our findings suggest that ED symptoms differ as a function of player position, and that elevated eating pathology in rugby players is associated with appearance comparison and exercise dependence. Despite the possible implications for prevention and treatment efforts, the clinical validity of the current findings must be confirmed with further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Within a particular sport, some positions may place a higher importance on weight‐status than other positions (e.g., coxswains in rowing). There is some evidence to suggest that certain positions in sport may be at higher risk for disordered eating compared to other positions (Compte et al, 2018; Torres‐McGehee et al, 2012). Uniforms vary considerably across different types of sports, ages, and levels of competition, and these differences could alter associated ED risk (Thompson & Sherman, 2014; Torres‐McGehee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Within a particular sport, some positions may place a higher importance on weight‐status than other positions (e.g., coxswains in rowing). There is some evidence to suggest that certain positions in sport may be at higher risk for disordered eating compared to other positions (Compte et al, 2018; Torres‐McGehee et al, 2012). Uniforms vary considerably across different types of sports, ages, and levels of competition, and these differences could alter associated ED risk (Thompson & Sherman, 2014; Torres‐McGehee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The practice of certain types of sports [e.g., esthetic and weight-category sports; ( 1 )] as well as the athlete’s position in the sport [e.g., striker; ( 25 )] is known to increase the risk of developing ED symptoms. Specifically, some sports may promote drive for thinness behaviors and attitudes in order to enhance athletic performance [e.g., esthetic sports; ( 1 , 26 )].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sundgot-Borgen and Garthe ( 28 ) reported that athletes in weight-category sports (e.g., boxing) tend to strive to develop muscularity while maintaining a low body weight. Regarding the athlete’s position, Compte et al ( 25 ) demonstrated that the position practiced in sport (e.g., attack or defense in some team sports) can influence drive for thinness behaviors and attitudes, depending on the associated athletic demands. Thus, depending on the demands of their sport or their position within it, athletes may develop behaviors and attitudes oriented not only toward the drive for thinness, but also toward the drive for muscularity ( 29 , 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…The practice of certain types of sports [e.g., esthetic and weightcategory sports; (1)] as well as the athlete's position in the sport [e.g., striker; (25)] is known to increase the risk of developing ED symptoms. Specifically, some sports may promote drive for thinness behaviors and attitudes in order to enhance athletic performance [e.g., esthetic sports; (1,26)].…”
Section: Introductionmentioning
confidence: 99%